PEMANFAATAN G SUITE FOR EDUCATION UNTUK MENINGKATKAN EFEKTIVITAS BELAJAR MENGAJAR SMA MUHAMMADIYAH JAKARTA UTARA - Supriatiningsih Supriatiningsih; Ndaru Ruseno; Lela Nurlela Wati; Suhana Suhana (Asosiasi Dosen Muda Indonesia, 2022)
Google provides some of its integrated application services under the name G Suite. G Suite is an integrated system that can be used for Gmail email-based institutional management which can also be accessed through a mobile application. This application also has an online learning management system facility called Google Classroom. Responding to the importance of this need, STIEMJ plans to provide assistance in migrating school email to G Suite for Education services, training in using email and G Suite for Education. To be able to use G Suite one of which requires institutional email settings that must be registered in advance for free with Google. After the school has a Google-based institutional email, the school will be able to take advantage of all the features of the applications owned by G Suite such as Google Docs, Google Sheets, Google Forms, Google Drive, Google Calendar and so on, including Google Classroom for online learning that it has. The problems to be solved with this community service are the need to increase teacher capacity in learning, the need for the introduction of G Suite for Education, setup of Google-based institutional email, and training on the use of Google Classroom for teachers. In this case, our PKM team intends to hold community service activities for teachers and students in utilizing the Google Form For Education application as a learning media and data processing for teachers and students at SMA Muhammadiyah North Jakarta.